Power Grid Planning and Operation Considering Electric Vehicle Proliferation - Murshudlu, Huseyn (ADA University, 2024)
In integrating electric vehicles into the power grid, a new milestone will be achieved towards the worldwide change in sustainable energy systems. Apart from altering the face of ground transportation, electric vehicles are foreseen to play a crucial role in modern power networks for enhancing grid flexibility, increasing renewable energy use, and thereby reducing green gas emissions. These end-consumers, electric by nature, are potentially units of energy storage that turn out to be the main contributors in the challenge of renewable intermittent and peak demand management. The research proposes a holistic approach to assess the integration of EVs into the power system of Azerbaijan. The study considers multiple electric vehicle penetration scenarios, user charging behaviors, infrastructure constraints, and renewable energy integration. The research work, based on ETAP software program and simulation-based approaches, investigates power flow, demand profiles, and voltage stability for the years 2030, 2040 and 2050. The results indicate remarkable challenges: overloading of the grid and voltage instability after 2040, especially in medium and low-voltage systems, with an estimated increase in peak demand of 523.2 MW by 2040 under high-penetration scenarios. The key results from this analysis include: (a) critical infrastructure constraints will begin to emerge from 2040, and there is a strategic need for investments in transmission and distribution networks; (b) the potential of demand-side management and V2G systems is necessary for maintaining stability on the grid; (c) clean energy sources such as solar and wind can contribute much to sustainable electric vehicle charging; (d) more robust public policies and financial incentives will be required for developing infrastructure readiness; and (e) the integration of variability in user charging behavior and in renewable energy availability needs consideration in long-term planning. In addition, this study is in line with the commitments of Azerbaijan during COP29 through providing actionable strategies toward a robust and sustainable energy system supportive of widespread EV adoption at lower greenhouse gas emissions. The methodology and findings give a foundation to the policymakers and industry leaders in Azerbaijan and other countries facing energy challenges.
Keywords: Electric vehicles -- Integration -- Azerbaijan.; Electric power systems -- Load dispatching -- Azerbaijan.; Electric vehicles -- Environmental aspects -- Azerbaijan.; Smart grids -- Azerbaijan.; Renewable energy sources -- Integration -- Azerbaijan.